Comparison of 3 Aging Metrics in Dual Declines to Capture All-Cause Dementia and Mortality Risk: Cohort Study - Anying Bai; Shan He; Yu Jiang; Weihao Xu; Zhanyi Lin (JMIR Aging)
Abstract BackgroundThe utility of aging metrics that incorporate cognitive and physical function is not fully understood. ObjectiveWe aim to compare the predictive capacities of 3 distinct aging metrics—motoric cognitive risk syndrome (MCR), physio-cognitive decline syndrome (PCDS), and cognitive frailty (CF)—for incident dementia and all-cause mortality among community-dwelling older adults. MethodsWe used longitudinal data from waves 10-15 of the Health and Retirement Study. Cox proportional hazards regression analysis was employed to evaluate the effects of MCR, PCDS, and CF on incident all-cause dementia and mortality, controlling for socioeconomic and lifestyle factors, as well as medical comorbidities. Discrimination analysis was conducted to assess and compare the predictive accuracy of the 3 aging metrics. ResultsA total of 2367 older individuals aged 65 years and older, with no baseline prevalence of dementia or disability, were ultimately included. The prevalence rates of MCR, PCDS, and CF were 5.4%, 6.3%, and 1.3%, respectively. Over a decade-long follow-up period, 341 cases of dementia and 573 deaths were recorded. All 3 metrics were predictive of incident all-cause dementia and mortality when adjusting for multiple confounders, with variations in the strength of their associations (incident dementia: MCR odds ratio [OR] 1.90, 95% CI 1.30‐2.78; CF 5.06, 95% CI 2.87‐8.92; PCDS 3.35, 95% CI 2.44‐4.58; mortality: MCR 1.60, 95% CI 1.17‐2.19; CF 3.26, 95% CI 1.99‐5.33; and PCDS 1.58, 95% CI 1.17‐2.13). The C-index indicated that PCDS and MCR had the highest discriminatory accuracy for all-cause dementia and mortality, respectively. ConclusionsDespite the inherent differences among the aging metrics that integrate cognitive and physical functions, they consistently identified risks of dementia and mortality. This underscores the importance of implementing targeted preventive strategies and intervention programs based on these metrics to enhance the overall quality of life and reduce premature deaths in aging populations.